Dye-sensitized LaFeO3 photocathode for solar-driven H2 generation. Issue 86 (10th October 2019) - Li, Fusheng; Xu, Rui; Nie, Chengming; Wu, Xiujuan; Zhang, Peili; Duan, Lele; Sun, Licheng
Abstract : A mesoporous visible-light-absorbing LaFeO3 semiconductor adsorbed an organic dye and a molecular catalyst on its surface for solar-driven H2 generation. Abstract : Mesoporous LaFeO3 was used as a p-type visible-light-absorbing semiconductor (VLAS) substrate for light-driven H2 generation. The successful modification of LaFeO3 with a molecular dye (P1* ) and a molecular hydrogen production catalyst (NiP ) paved a novel way to construct DS-PEC photocathodes for solar-driven H2 generation by using VLASs.